2008
DOI: 10.1038/embor.2008.132
|View full text |Cite
|
Sign up to set email alerts
|

PCSK9 is required for the disposal of non‐acetylated intermediates of the nascent membrane protein BACE1

Abstract: We have recently identified a new form of post-translational regulation of BACE1 (b-site amyloid precursor protein (APP)-cleaving enzyme 1), a membrane protein that acts as the rate-limiting enzyme in the generation of the Alzheimer disease amyloid b-peptide (Ab). Specifically, BACE1 is transiently acetylated on seven lysine residues in the lumen of the endoplasmic reticulum/endoplasmic reticulum-Golgi intermediate compartment (ER/ERGIC). The acetylated intermediates of the nascent protein are able to reach th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
87
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(92 citation statements)
references
References 22 publications
4
87
1
Order By: Relevance
“…PCSK9 was reported to contribute to the disposal of nonacetylated BACE1. 73 This interesting observation still requires in vivo validation. (2) In the second example, within the ER/ER-Golgi intermediate compartment of cells, PCSK9 was reported to enhance the degradation of the epithelial Na + channel (ENaC) that is critical for Na + homeostasis and blood pressure control.…”
Section: Other Pcsk9 Target Proteinsmentioning
confidence: 99%
“…PCSK9 was reported to contribute to the disposal of nonacetylated BACE1. 73 This interesting observation still requires in vivo validation. (2) In the second example, within the ER/ER-Golgi intermediate compartment of cells, PCSK9 was reported to enhance the degradation of the epithelial Na + channel (ENaC) that is critical for Na + homeostasis and blood pressure control.…”
Section: Other Pcsk9 Target Proteinsmentioning
confidence: 99%
“…For example, reversible acetylation in the luminal domain of BACE1 regulates its stability as well as exit from the ER (20,57). Moreover, phosphorylation regulates the fate of BACE1 endocytosed from the cell surface; whereas phosphorylated BACE1 is transported from the endosomes to the TGN, non-phosphorylated BACE1 is directly recycled to the cell surface (18,29).…”
Section: Bace1 Is S-palmitoylated At 4 Cysteine Residues-previ-mentioning
confidence: 99%
“…It has also been recently shown that overexpression of PCSK9 in cells decreased cellular levels of the ␤ -site amyloid precursor protein (APP)-cleaving enzyme 1 (BACE1), a membrane protease responsible for the production of toxic ␤ -amyloid peptides (A ␤ ) that accumulate in neuritic plaques of AD brains ( 27,28 ). In the present study, we investigated whether PCSK9 participates in the regulation of the steady-state levels of LDLR, VLDLR, and ApoER2, as well as BACE1 in the adult mouse brain.…”
Section: Mutant Mouse Line Establishmentmentioning
confidence: 99%